2005
DOI: 10.1007/s11199-005-4195-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Gender Differences in Partner Violence: Implications from Research on Other Forms of Violent and Socially Undesirable Behavior

Abstract: The proposition that men and women perpetrate partner violence equally would make partner violence unique with respect to other forms of interpersonal violence. Women, however, commit a substantial minority of violent acts. Any theory of gender patterns in partner violence needs to be reconciled with other violence data. Data on other violence indicate that different methodologies sample from different sets of phenomena, and those methods that sample the least severe violence show greater gender equivalence. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 64 publications
(103 reference statements)
3
108
1
2
Order By: Relevance
“…Specific to domestic relationships, however, researchers have found that men and women use aggression with similar frequency (e.g., Bookwala, Sobin, & Zdaniuk, 2005). However, Bookwala et al reported that the injuries inflicted by violence differed for men and women, with men inflicting more severe injuries and being more likely to kill their partner (see also Hamby, 2005). Furthermore, the Bureau of Justice Statistics (Langan & Dawson, 1995) indicates that women are at a greater risk than are men of being killed by an intimate partner.…”
Section: Hands-on Killingmentioning
confidence: 99%
“…Specific to domestic relationships, however, researchers have found that men and women use aggression with similar frequency (e.g., Bookwala, Sobin, & Zdaniuk, 2005). However, Bookwala et al reported that the injuries inflicted by violence differed for men and women, with men inflicting more severe injuries and being more likely to kill their partner (see also Hamby, 2005). Furthermore, the Bureau of Justice Statistics (Langan & Dawson, 1995) indicates that women are at a greater risk than are men of being killed by an intimate partner.…”
Section: Hands-on Killingmentioning
confidence: 99%
“…Thus, because studies have tended to focus on only one form of aggression, it remains unclear whether the pattern of potential risk factors or markers would be different for different forms of aggression. For example, it has been suggested that it is essential to measure psychological aggression and injury, in addition to physical aggression, to obtain a better understanding of the relationship between gender and violence (Hamby, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…But using too detailed descriptions can lead to the risk of some behaviours/events not being reported because they are not included in the description. Also, using too many questions can lead to 'reporting load', meaning that respondents avoid reporting incidents because they want the interview to finish faster (Hamby, 2005).…”
Section: Defining Labelling and Operationalizing Violencementioning
confidence: 99%
“…The field of intimate partner violence has struggled with challenges concerning content and construct validity of survey instruments for a long time (Hamby, 2005;Follingstad and Rogers, 2013;Follingstad and Ryan, 2013;Woodin et al, 2013;Hamby, 2014a). One fundamental challenge is what kind of instruments should be used.…”
Section: Behavioural Checklistsmentioning
confidence: 99%
See 1 more Smart Citation